Struktur Modal, Profitabilitas dan Nilai Perusahaan - Jesselyn Hartono; Elfina Astrella Sambuaga (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
This study was conducted to analyze the relationship between capital structure, profitability and firm value. Firm Value as measured by PBV (Price to Book Value). The capital structure is proxied using a debt to asset ratio and profitability using ROA (return on assets). The data used are secondary data in the form of financial reports of the Consumer Goods Industry from the top five countries with the highest GDP in Southeast Asia, namely: Indonesia, Singapore, Thailand, Malaysia and the Philippines for the period 2014 to 2018. The data processing technique is carried out using multiple regression analysis. The results of this study differ between countries, one of which is influenced by the policies in force in each country.